INVESTIGATING THE RELATIONSHIP BETWEEN SELF-CONTROL, CELEBRITY WORSHIP, AND ADOLESCENTS MENTAL HEALTH: Self Control, Celebrity Worship and Mental Health in Adolescents - Indraswari, Febrina Ayu; Tristiana, S.Kep.Ns.M.Kep, Rr Dian; Wahyuni, Sylvia Dwi (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2025)
Introduction: Many adolescents reported experiencing anxiety, stress, and depression due to poor time management and obsessive celebrity worship. This study aimed to explore the connection between self-control, celebrity worship, and mental health in adolescent K-pop fans. Methods: The research employed a quantitative approach with a correlative study design and a cross-sectional methodology. A total of 117 adolescent K-pop fans were selected using purposive sampling. The independent variables were self-control and celebrity worship, while mental health was the dependent variable. The Self-Control Scale (SCS) questionnaire, the Celebrity Attitude Scale (CAS), and the Mental-Health Inventory-38 (MHI-38) were used for data collection. Data analysis was performed using the Spearman Rho test at a significance level of <0.05. Results: The majority of late teens who are K-Pop fans demonstrate moderate levels of self-control (72.6%), moderate celebrity worship (76.9%), and mild mental health (71.8%). The research highlights a significant relationship between self-control and celebrity worship (p<0.05, r= -0.207) and mental health (p<0.05, r=0.287) in adolescent K-Pop fans, and celebrity worship (p<0.05, r= -0.213) was related to mental health in adolescent K-Pop fans. Conclusion: Higher self-control is associated with lower celebrity worship and better mental health, whereas excessive celebrity worship is linked to poorer mental health. Awareness is needed from parents, schools, and health workers to engage with adolescents to help them recognize celebrity worship behaviors, promote self-control, cope with stress, maintain sound mental well-being, and set clear future goals.